Farmers’ perception on climate change, soil erosion and adaptation strategies in small rural communities of Mali: case study of the rural municipality of Méguétan - Mahamadou Lamine Katilé; Aboubakar Bengaly; Souleymane Sidi Traoré; Jesús Rodrigo-Comino (Investigaciones Geográficas)
The impacts of climate change and soil erosion are significantly affecting agriculture in non-developed countries. In Mali, a country located in Western Africa, there is a drastic reduction in available fertile arable lands and water scarcity, which is damaging rural communities and affecting the development of vital infrastructures, consequently, decreasing people’s incomes. There is a lack of information about the perception of these challenges among the small rural communities and the possible adaptation strategies can be applied. Therefore, the main aim of this study was to determine local farmer perceptions of climate change, soil erosion, and adaptation strategies conducting a survey among 200 farmers in 10 villages within the rural municipality of Méguétan, serving as a representative study case. Our results showed that farmers are aware of the challenges related to climate change and soil erosion and are willing to adopt some measures but conditioned by a range of traditional techniques. The most common strategies are: changing the sowing calendar, diversifying crops, using resistant varieties, having an alternative income, and following weather forecasts on the radio. Stone rows remain the most widely adopted technique to reduce soil erosion, with a knowledge rate of 88% and an application about 29%. The study also highlighted the increasing vulnerability of farmers to climate change and soil erosion due to insufficient material and financial resources. We conclude policies should pay attention to services and partners that invest more funds in technical assistance to strengthen adaptation strategies and teach the population, considering nature-based solutions.